Misrepresentation and migration - Anders Kärnä; Patrik Öhberg (Research Institute of Industrial Economics (IFN), 2023)
In a representative democracy politicians should either implement policies that voters want or policies that politicians believe are in voters long-term interest, even if voters currently oppose them. While the exact balance between these goals is debatable, politicians can also have strong preferences for certain policies. Politicians' policy engagement can tempt them to dismiss voters' preferences and resist information counter to their own policy position. In this paper, we discuss Sweden's generous migration policy and how it can serve as an example where politicians' policy engagement led them to a overly optimistic view of the implications of welcoming a large influx of refugees. Using detailed, repeated, survey data on members of parliament, we show that Swedish politicians favored a much more generous policy towards accepting refugees than voters for a long period of time. Neither observable factors nor expert knowledge can explain this difference between voters and politicians. A more likely explanations is wishful thinking and policy engagement from politicians that continued until political competition increased.
Keywords: P16; O15; P35; 330; Political Misrepresentation; Immigration Policy; Moral Psychology; Political Failure